Brassinosteriod Insensitive 2 (BIN2) acts as a downstream effector of the Target of Rapamycin (TOR) signaling pathway to regulate photoautotrophic growth in Arabidopsis. Issue 1 (1st August 2016) - Xiong, Fangjie; Zhang, Rui; Meng, Zhigang; Deng, Kexuan; Que, Yumei; Zhuo, Fengping; Feng, Li; Guo, Sundui; Datla, Raju; Ren, Maozhi
Summary: The components of the target of rapamycin (TOR) signaling pathway have been well characterized in heterotrophic organisms from yeast to humans. However, because of rapamycin insensitivity, embryonic lethality in tor null mutants and a lack of reliable ways of detecting TOR protein kinase in higher plants, the key players upstream and downstream of TOR remain largely unknown in plants. Using engineered rapamycin‐sensitive Binding Protein 12‐2 (BP12‐2) plants, the present study showed that combined treatment with rapamycin and active‐site TOR inhibitors (asTORis) results in synergistic inhibition of TOR activity and plant growth in Arabidopsis. Based on this system, we revealed that TOR signaling plays a crucial role in modulating the transition from heterotrophic to photoautotrophic growth in Arabidopsis. Ribosomal protein S6 kinase 2 ( S6K2 ) was identified as a direct downstream target of TOR, and the growth of TOR‐suppressed plants could be rescued by up‐regulating S6K2 . Systems, genetic, and biochemical analyses revealed that Brassinosteriod Insensitive 2 ( BIN2 ) acts as a novel downstream effector of S6K2, and the phosphorylation of BIN2 depends on TOR‐S6K2 signaling in Arabidopsis. By combining pharmacological with genetic and biochemical approaches, we determined that the TOR‐S6K2‐BIN2 signaling pathway plays important roles in regulating the photoautotrophic growth of Arabidopsis.